2021
DOI: 10.4018/978-1-7998-7876-6.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teachers' Beliefs About Listening in a Foreign Language

Abstract: There is a substantial amount of research in the field of language teacher cognition reiterating that teachers' beliefs influence their classroom practices; however, teacher beliefs and practices do not always correspond because of the differences in both researchers' and teachers' conceptualization of beliefs and practices. This study aims to investigate the beliefs and practices of 96 language teachers in Turkey. A mixed-method research design was employed to answer the questions to what extent teachers' bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…An early study conducted by Lucas and Schecter 71 has already reported an inconsistency between teachers’ cognition and practices in terms of equity, claiming that though teachers self-reported to be well aware of equity, what they do in the classroom is a different story. The mismatch between teacher cognition and practices is further supported by more recent studies done by Erling et al, 40 Irgin 72 and Sulistyowardani et al 41 …”
Section: Literature Reviewmentioning
confidence: 71%
“…An early study conducted by Lucas and Schecter 71 has already reported an inconsistency between teachers’ cognition and practices in terms of equity, claiming that though teachers self-reported to be well aware of equity, what they do in the classroom is a different story. The mismatch between teacher cognition and practices is further supported by more recent studies done by Erling et al, 40 Irgin 72 and Sulistyowardani et al 41 …”
Section: Literature Reviewmentioning
confidence: 71%
“…That is, teachers' equitybound cognition is a prerequisite that can guarantee equitable practices. In contrast to this statement, a growing body of studies (Chen and Vibulphol, 2019;Wei and Cao, 2020;Irgin, 2021;Wu et al, 2021) has found a distinctive mismatch between EFL teachers' cognition and practices; this dissonance is also reflected in teachers' cognitions and practices toward equity (Erling et al, 2021).…”
Section: Empirical Studies Concerning the Interrelation Between Equit...mentioning
confidence: 79%